Women in Thanphuying La-iad Phibunsongkhram’s Rumwong Songs - Chutintaranond, Thanasin (Journal of Thai Studies, 2023)
This article aims to detail an analysis of women’s qualifications in the lyrics of six rumwong songs’ that were composed by Thanphuying La-iad Phibunsongkhram. The results found that these songs represent three desired qualifications of Thai women during the World War II era. 1) Thai women should carry on Thai conventional of beauty. The lyrics disclose clear metaphorical comparisons from Thai literature convention that typically compares the beauty of women to the beauty of the moon. Moreover, good manners and good rhetoric are needed. 2) Thai women should be a flower of the nation. In accordance with the war situation, Thailand could not deny women power since everyone in the nation, whether man or woman, had a vital duty to protect the nation. This was related to the government’s policy to establish a female military school. 3) Thai women should love only patriotic men. While the lyrics admired the beauty of women, for men, faithfulness and patriotism to the nation were required. These qualifications are important and significant for women to consider before they chose their lover. Nevertheless, the composer intended to use the six rumwong songs as cultural entertainment to lead the society by harmoniously transmitting some political messages through the lyrics.